Strategy to Accelerate The Implementation of The Internal Quality Assurance System in Private Higher Education in LLDIKTI IV in West Java and Banten Regions - Rahminawati, Nan; Amaranti, Reni; Supangat, Ivan (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Improving the quality of higher education is one of the strategic priorities in developing competitive human resources. The Internal Quality Assurance System (SPMI) is the main mechanism mandated by Permendikbud Number 53 of 2023 to ensure the quality of higher education services in accordance with the National Higher Education Standards (SN-Dikti). This study aims to examine the strategy of the Higher Education Service Institution (LLDIKTI) IV of West Java and Banten in accelerating the implementation of SPMI in Private Universities (PTS). This research method uses a qualitative descriptive approach with data collection through interviews, document studies, and field observations. The results of this study conclude that SPMI Clustering in the red, yellow, and green zones is an important instrument in mapping the readiness and progress of quality implementation in private universities in LLDIKTI IV. Universities in the red zone face major challenges in compiling and reporting SPMI documents, while universities in the yellow zone already have documents but are not yet fully complete or validated. On the other hand, universities in the green zone have met all reporting requirements and have a more established quality system. As a form of support, LLDIKTI IV has taken various acceleration steps, including the SPMI Clinic, the Regional Facilitator Assistance Program, and various SPMI innovations, such as the development of the SPMI Dashboard, the SPMI Guidelines, and award mechanisms for facilitators and the best universities. Through these steps, it is hoped that more universities will be able to move from the red and yellow zones to the green zone, so that the quality of higher education in the LLDIKTI IV region continues to improve and become more competitive.